EFEKTIVITAS PELAKSANAAN PERATURAN DAERAH PROVINSI BALI NOMOR 5 TAHUN 2008 TENTANG PRAMUWISATA YANG BERTUJUAN UNTUK MENGURANGI ANGKA PRAMUWISATA ILEGAL - Novita Yani, Isma; Ariani, I Gusti Ayu Agung (Kertha Negara : Journal Ilmu Hukum; Vol. 01, no. 01, Maret 2013, 2013)
The Violation of tourism in Bali is currently happening covers from various sectors of tourism, which is one of the sector is a guide as an intermediary deliver an explanation about existing attractions in Bali to tourists who are visiting. There are several requirements that are listed to be a legal guide, which has been set in the Bali Provincial Regulation No. 5 in 2008 about the Guides. The problems that occurred, the first is how the effectiveness of the Bali Provincial Regulation No. 5 in 2008 in province of Bali, the second is what kind of factors which is become a barriers to effective implementation of Bali Provincial Regulation No. 5 in 2008 in province of Bali. Conducted legal research is empirical legal research, which use techniques data collecting that is interview. Conclusions from the study showed that the number of offenses committed by the guides in the province of Bali is still in existence. The main limiting factor is the Human Resources (HR) which is still inadequate, so under the supervision of the guides is so weak.
Keywords: Effectiveness, illegal guides, requirements, the tourist.